„Czemu młodości nie dał mi Bóg, tej płochej, lekkiej, swawolnej?” — rozrachunek z życiem w twórczości Marii Bartusówny - Jabłońska, Joanna (Starość i młodość w literaturze i kulturze, 2016)
The problems of youth and old age are important motives in the works of Maria Bartusówna. Youth,symbolising a time of joy, madness, carelessness, sometimes stupidity in the works of the deceased at theage of 31 years the poet is seen as a time of suffering, pessimism and doubt. Autumn, as old age is associatedwith sadness, despair, loneliness, pain and death. In a series of sonnets entitled Prenuptial ThoughtsBartusówna presented the internal conflict of a young girl. On one side there is a convention and theduty to ensure the material existence for himself and his mother. Among the values specific to the time ofyouth there are: freedom, love, happiness individual units. In both cycle of Prenuptial Thoughts and songsfrom volume Poems motives of youth and old age are interweared. It seems that the poet was markedby the problem of the old age in adolescence, because of her youth accompanied by incessant sufferingcaused by the death of loved ones, unhappy love, the incapability to realise her dreams, financial problems and severe disease causing death at a young age.